2020
DOI: 10.1111/ene.14440
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of smell recovery in 751 patients affected by the COVID‐19 outbreak

Abstract: Background and purpose: Post-viral olfactory dysfunction is well established and has been shown to be a key symptom of COVID-19 with more than 66% of European and US patients reporting some degree of loss of smell. Persistent olfactory dysfunction appears to be commonplace and will drive the demand for general practitioner, otolaryngology or neurology consultation in the next few monthsevidence regarding recovery will be essential in counselling our patients. Methods: This was a prospective survey-based data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 8 publications
7
135
2
2
Order By: Relevance
“…In a subgroup of patients who had OD at the time of presentation to referral centres, 58.8% were nearly or fully recovered. In a study by Chiesa-Estomba et al [17], 367 (49%) out of 751 patients were completely recovered from OD after a mean follow-up of 47 ± 7 days. Victor Gorzkowski et al [18] also reported in a study on 229 patients with COVID-19, 78.4% of patients were recovered within the fourth and the fifteenth day after olfactory loss onset with a complete olfactory recovery in 51.43% of patients.…”
Section: Discussionmentioning
confidence: 91%
“…In a subgroup of patients who had OD at the time of presentation to referral centres, 58.8% were nearly or fully recovered. In a study by Chiesa-Estomba et al [17], 367 (49%) out of 751 patients were completely recovered from OD after a mean follow-up of 47 ± 7 days. Victor Gorzkowski et al [18] also reported in a study on 229 patients with COVID-19, 78.4% of patients were recovered within the fourth and the fifteenth day after olfactory loss onset with a complete olfactory recovery in 51.43% of patients.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
“…However, the persistence of olfactory dysfunction was reported for 277 patients (37%). The data obtained was subjective, since information on patients was acquired by questionnaires and follow-up was carried out via telemedicine [ 26 ]. In their study, Gelardi et al [ 27 ] reported that sensory symptoms lasted an average of 16.1 days (range 7–22 days), and of the patients, 37% completely recovered, 33% partially recovered, and 30% did not recover.…”
Section: Discussionmentioning
confidence: 99%